Exposure to Refugees and Voting for the Far-Right. (Unexpected) Results from Austria - Andreas Steinmayr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The massive increase in the number of arriving refugees in Europe in 2015 creates enormous economic and political challenges in the receiving countries. An important concern is that the inflow of refugees increases the support for far-right, nationalist, anti-immigration parties. This paper studies a natural experiment in an Austrian state to identify the causal effect of exposure to refugees in the neighborhood on the support for the far-right Freedom Party of Austria (FPÖ). Before the local and state elections in September 2015 the inflow of refugees dominated the entire pre-electoral discussion and the FPÖ - with a fierce anti-asylum campaign - doubled its vote share in this election. At the time of the election, 42 percent of Upper Austrian communities hosted refugees, which provides variation in the exposure to refugees at the community level. To account for the potential endogeneity in the distribution of refugees, I use the availability of existing group accommodations as instrumental variable. To cope with the sudden inflow of large number of refugees, these buildings were used as accommodation and their existence strongly increases the probability of refugee presence. In line with the contact hypothesis I find that hosting refugees in the community decreases the support for the FPÖ by 4.42 percentage points in state elections and increases the optimism in the population that the integration of refugees can be managed. The effects are robust to a series of sensitivity and placebo checks.
Keywords: D72; J15; P16; 330